2020
DOI: 10.19102/icrm.2020.111203
|View full text |Cite
|
Sign up to set email alerts
|

First Demonstration of Cardiac Resynchronization Therapy Defibrillator Service Life Exceeding Patient Survival in a Heart Failure with Reduced Ejection Fraction Cohort

Abstract: The occurrence of patient longevity exceeding implantable cardioverterdefibrillator (ICD) service life has important implications for patient outcomes and the cost of care. Battery capacity as measured in ampere-hours (Ah) is a strong predictor of survival to an elective replacement indicator (ERI) point and 2.1 Ah is the largest-capacity ICD battery in use at our facility. This was a long-term study of ICDs out of service (OOS) in patients with heart failure with reduced ejection fraction who received a 2.1-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Prior research has reported that CRT-D extended battery life exceeded patient survival in a typical heart failure cohort with reduced ejection fraction. 7 Extended longevity CRT-D devices not only outlast average patient life expectancy, they also avoid costs of generator changes and associated complications.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has reported that CRT-D extended battery life exceeded patient survival in a typical heart failure cohort with reduced ejection fraction. 7 Extended longevity CRT-D devices not only outlast average patient life expectancy, they also avoid costs of generator changes and associated complications.…”
Section: Introductionmentioning
confidence: 99%